ASSESSING HEALTH-RELATED QUALITY OF LIFE AMONG TUBERCULOSIS PATIENTS: A CROSS-SECTIONAL STUDY IN KUPANG, INDONESIA - Imelda Februati Ester Manurung; Christina Nayoan; Apris A. Adu; Yendris K. Syamruth; Ofelia do Carmo; Agus Fitriangga (Universitas Airlangga, 2026)
Introduction: The target success rate of tuberculosis (TB) treatment has yet to reach 90%. Improving the quality of life (QoL) is crucial to support successful TB treatment, with patient-centered care playing a significant role in addressing individual needs and enhancing treatment adherence. Aims: This study aimed to identify determinants associated with poor quality of life among TB patients. Methods: A cross-sectional study was conducted among 102 TB patients in Kupang, selected through convenience sampling. Measurement of quality of life using WHOQOL-BREF by assessing physical, psychological, social relations and environmental aspects. Multivariable binomial logistic regression was performed to identify factors independently associated with poor QoL. Results: 52.90% of TB patients had poor quality of life. TB patients with comorbid history (OR: 4.05; CI 95%: 1.180 - 13.927), BMI (OR: 3.14; CI 95%: 1.195 - 8.250) and treatment phase (OR: 4.93; CI 95%: 1.166 - 20.898) were independently associated with poor quality of life. Conclusion: Comorbid history of HIV or DM, BMI < 18.5 and intensive treatment phase were significant determinants of poor QoL among TB patients. It is important to provide assistance for TB patients based on the categories of factors that affect quality of life. Targeted interventions addressing these factors may reduce the burden of poor QoL and improve TB treatment outcomes.